Review of Writing Centres in Higher Education: Working in and across the disciplines - Moore, Jean Matier (Journal of Academic Writing, 2021)
This is a review of Writing Centres in Higher Education: Working in and across the disciplines, edited by Sherran Clarence and Laura Dison.